Articulo ¿Cómo se ha potencializado el E-commerce en tiempos de pandemia ? (2021)
This research analyzes the topic of electronic commerce before and during the health emergency presented in 2020, at national and international level, showing figures of the use of tools within commerce. It also explains the steps to implement e-commerce in companies, the benefits that can be obtained from it. Considering that e-commerce can be considered as a new marketing strategy that should be implemented with new and different features of business ideas, This article considers that e-commerce is a marketing drive strategy for the exchange of goods and services that must be coupled with other distribution channels. For them the following specific objectives are developed (i) examine the use of e-commerce and its impact on the gross domestic product (GDP) between the last five years (ii) identify the advantages and the possible access of e-commerce with which Colombia has (iii) Establish strategies for the implementation of e-commerce in companies, using a quantitative descriptive research methodology.